1998
DOI: 10.1111/j.1600-0447.1998.tb09996.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental health problems among homeless adolescents

Abstract: This paper reviews 18 surveys of mental health problems among homeless adolescents and reports on a pilot study of the same topic conducted in Amsterdam. Sampling methods and measures of mental health are discussed. The reported estimates of mental health problems vary greatly, very probably because of methodological differences. Despite the different methods used, there seems to be considerable research evidence to support a high prevalence of mental disorders among homeless adolescents. The results of the pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 24 publications
0
13
0
5
Order By: Relevance
“…For homeless adolescents, lifetime suicide attempt rates have ranged from 18% (Yates et al 1988) to 53% (Smart and Ogborne 1994), and lifetime suicidal ideation rates have been as high as 28% (Booth and Zhang 1996) to 62% (Unger et al 1997). Also, the lifetime rate of one (or more) psychiatric disorders ranges from 78% (Sleegers et al 1998) to 90% (Feitel et al 1992).Our review also suggests where research on suicidality and internalizing and externalizing disorders can be improved. No previous studies on suicidality and that defines internalizing and externalizing disorders broadly have used confirmatory factor analysis (CFA; Breton et al 2002;Esposito and Clum 2003;Hills et al 2005;Verona et al 2004).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…For homeless adolescents, lifetime suicide attempt rates have ranged from 18% (Yates et al 1988) to 53% (Smart and Ogborne 1994), and lifetime suicidal ideation rates have been as high as 28% (Booth and Zhang 1996) to 62% (Unger et al 1997). Also, the lifetime rate of one (or more) psychiatric disorders ranges from 78% (Sleegers et al 1998) to 90% (Feitel et al 1992).Our review also suggests where research on suicidality and internalizing and externalizing disorders can be improved. No previous studies on suicidality and that defines internalizing and externalizing disorders broadly have used confirmatory factor analysis (CFA; Breton et al 2002;Esposito and Clum 2003;Hills et al 2005;Verona et al 2004).…”
mentioning
confidence: 83%
“…For homeless adolescents, lifetime suicide attempt rates have ranged from 18% (Yates et al 1988) to 53% (Smart and Ogborne 1994), and lifetime suicidal ideation rates have been as high as 28% (Booth and Zhang 1996) to 62% (Unger et al 1997). Also, the lifetime rate of one (or more) psychiatric disorders ranges from 78% (Sleegers et al 1998) to 90% (Feitel et al 1992).…”
Section: Contributions Of the Present Studymentioning
confidence: 99%
“…There is now a wealth of evidence from a range of countries demonstrating that, in comparison to their home-based peers, homeless young people use more drugs, use these drugs more often, and are dramatically more likely to inject (Bailey, Camlin, & Ennett, 1998;Fors & Rojek, 1991;Greene, Ennett, & Ringwalt, 1997;Holtzman et al, 1991;Kral, Molnar, Booth, & Watters, 1997;Rosenthal et al, 2005;Rosenthal, Moore, & Buzwell, 1994;Smart, Adlaf, Walsh, & Zdanowicz, 1994;Yates, MacKenzie, Pennbridge, & Cohen, 1988). Similarly, a review of surveys of mental health problems of homeless adolescents concluded that there was a high rate of mental disorders among homeless young people (Sleegers, Spijker, & van Limbeek, 1998). Homeless young people are more likely to attempt suicide and to engage in self-harm (Desai, Liu-Mares, Dausey, & Rosenheck, 2003;Rew, Taylor-Seehafer, & Fitzgerald, 2001; substance abuse problems among this population.…”
Section: Introductionmentioning
confidence: 92%
“…Although prevalence rates of psychological disturbance vary widely among samples of homeless adolescents (Sleegers, Spijker, van Limbeek, & van Engeland, 1998), it is well documented that this population is at higher risk than the general adolescent population for many mental health issues (Craig & Hodson, 1998; Unger, Kipke, Simon, Montgomery, & Johnson, 1997; Whitbeck, Johnson, Hoyt, & Cauce, 2004). In fact, about two-thirds of homeless adolescents have at least one psychiatric disorder meeting DSM IV-R criteria (Cauce et al, 2000; Craig & Hodson, 1998).…”
Section: Mental Health Of Homeless Adolescentsmentioning
confidence: 99%